Fibroadenoma in axillary accessory breast: a case report - Laporte, Bruno Eduardo Pereira; Salgado, Hakayna Calegaro; Monteze, Nathália Mussi; Rangel, João Matheus de Castro; Carvalho, Miralva Aurora Galvão; Esperança, Samuel Drumond (Mastology, 2020)
The mass are among the possible alterations observed in the axilla. When found, the most frequent differential diagnosis are lymphadenopathy, metastatic lymphadenomegaly, lymphoma, lipoma or tumors in the apocrine glands. Besides that, the presence of accessory breast tissue must also be considered and, as the topical breast tissue, can be the target of breast diseases, either benign or malignant. Female patient, 23 years old, with the presence of hardened palpable node in the right axilla. At the ultrasound, it presented characteristics that classified it as Bi-Rads® 4. An aspiration biopsy of the node was performed with fine-needle, which resulted in unsatisfying material. After the explanation of the therapeutic choices, the patient opted for the excision of the axillary node. The anatomical pathological result showed a nodular formation compatible with fibroadenoma. The occurrence of a node in the axillary region is common. However, in the vast majority of times, it is merely an inflammatory response, manifested as a lymphadenomegaly. In case of chronic mass with suspicious characteristics, it is convenient to suspect the presence of lymphoid neoplasms, locoregional metastasis of breast cancer or melanoma and alterations in accessory breast tissue. In young patients, it is important to evaluate the existence of accessory breast tissue with the presence of suspicious axillary node, because, although controversial, some authors believe that such alterations occur more frequently in these patients. Additionally, in cases of inconclusive imaging, an excision of the lesion must be performed for a definite diagnosis.